ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN PHBS SISWA SDI WAIRKLAU DI KABUPATEN SIKKA - Gonsalfina Dua Sareng Gonsal (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Cleans and Health Living Behavior (PHBS) is an initiative to enable students, teachers, and the school community to know, want, and be able to improve their own health status and the school environment. The implementation of PHBS by elementary school students will reduce the risk of being infected with environmental-based health problems such as diarrhea, as well as familiarize students with a healthy lifestyle, but the implementation of PHBS in elementary students is low, there are many factors related. The purpose of this study is to determine factors related to the implementation of PHBS for SDI Wairklau students at Sikka Regency. The research design is an analytic survey, cross sectional and analize by fisher exact test with α = 0.05. The sample used 101 students of classess V and VI, use simple random samplingObtain information using questionnaires and observational interviews. The results; there are a relations between student knowledge with student PHBS, student attitudes with student PHBS, and school sanitation facilities with student PHBS, and no relation between teacher support and student PHBS. The conclusion is that a variety of elements are involved in changing behavior of non-PHBS into PHBS in students, so to get the right element, it is necessary to intervene both on students (internal) and external factors or elements such as sanitation facilities.